(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
Performance of salt-tolerant Boro rice was investigated under the interaction effect of variety and different doses of potassium fertilizer, which is a part of the research for developing agriculture in coastal areas of Bangladesh. A field experiment was conducted at the research field of Agriculture department, Noakhali Science and Technology University (NSTU), Noakhali-3814. The experiment was carried out in a Randomized Complete Block Design (RCBD) with three replications where two varieties viz. BINA dhan-8, BRRI dhan-28 and three doses of potassium viz. 120 kg/ha, 84 kg/ha and 36kg/ha were used as treatments. Plant height (cm), tillers/hill, grain/panicle, 1000 grain weight (g), grain yield (t/ha), straw yield (t/ha) and harvest index (%) were compared among varieties and treatments. Results revealed that only variety and only potassium fertilizer had non-significant influence but the interaction of variety and potassium fertilizer had a significant effect on the performance of salt-tolerant Boro rice. Therefore, the present study suggests that salt-tolerant BINA dhan-8 variety may be cultivated with 120 kg potassium/ha for obtaining higher yield in the southern coastal area of Bangladesh. Asian Australas. J. Biosci. Biotechnol. 2020, 5 (1), 21-26